Outdoor nighttime light exposure (light pollution) is associated with Alzheimer’s disease - Voigt, Robin M.; Ouyang, Bichun; Keshavarzian, Ali (Frontiers in Neuroscience, 2024)
Alzheimer's disease (AD) prevalence has increased in the last century which can be attributed to increased lifespan, but environment is also important. This study evaluated the relationship between outdoor nighttime light exposure and AD prevalence in the United States. Higher outdoor nighttime light was associated with higher prevalence of AD. While atrial fibrillation, diabetes, hyperlipidemia, hypertension, and stroke were associated more strongly with AD prevalence than nighttime light intensity, nighttime light was more strongly associated with AD prevalence than alcohol abuse, chronic kidney disease, depression, heart failure, and obesity. Startlingly, nighttime light exposure more strongly associated with AD prevalence in those under the age of 65 than any other disease factor examined. These data indicate a need to investigate how nighttime light exposure influences AD pathogenesis.